The Relationship of Personal Hygiene with the Incident of Scabies in Bumi Tamalanrea Orphanage Makassar - Bachri, Syaiful; Lonik, Lorensius; Nurhaedah, Nurhaedah; Wicaksono, Rizky Rahadian; Hanif, Muhammad; Timisela, Joula (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The process of child growth and development is divided by age, one of which is the preschool phase. The growth and development of children at this age is very rapid, including cognitive, biological, spiritual and psychosocial development. With the rapid growth and development, education is very important to be given to form the foundation, build the personality, mentality and character of children, one of the important educations is to provide personal hygiene. Children's personal hygiene is an important aspect that includes personal hygiene from head to toe as a whole. The form of children's skills related to personal hygiene is the child's ability to control defecation and urination properly and regularly to avoid health problems, one of which is scabies. Scabies is a contagious disease caused by the infestation of Sarcoptes scabiei hominis variant on the skin which is characterized by itching and skin eruptions. The purpose of the study was to determine the relationship personal hygiene with the incidence of scabies. This type of research is quantitative with a cross-sectional study design. This study uses a total sampling technique. Data analysis used is univariate and bivariate analysis with the Chi Square test. The results of this study found that there was a significant relationship between personal hygiene and the incidence of scabies. The conclusion is that there is a relationship personal hygiene with the occurrence of scabies. It is recommended that party The nearest health center for Providing health education about personal hygiene has a positive impact, namely increase knowledge about personal hygiene leads to behavior or action under maintenance self Which Good, so that incident rate scabies can be minimized as much as possible.